Sarzameen-e-Hazara Ka Munfarid Geet Nigar Qateel Shifai - Ur Rehman, Mati; Hashmi, Munawar (sourcecoder, 2022)
Hazara is such a unique landscape of Pakistan, which majestic charms are matchless, some prolific and towering literary personalities are related to it, who upheld song writing in Urdu.such as Qateel Shifai, Bashir Haider, Kanwal, Akhtar Bekhud muradabadi etc. So, it is pertinent that such unexplored pearls should be relocated that to what extent they contributed in song writing. So it is essentially worthwhile that such efforts in poetry of songs of Hazara region should be captured through the lens of research and on modern scientific ground. Song is a representation of culture and civilization, sentiments and feelings, desires and wishes, ideas and thoughts, rites and customs of any landscape. There is no peculiar disposition of song, everything depends upon intent and mode of the poet, the way he/she composes verse line or couplet and how the poet compose and rhyme scheme, and its length. Hazara is such a unique landscape of Pakistan, whose majestic charms are matchless, so prolific and towering literary personalities are related to it, who upheld song writing in Urdu.